AGAINST POST-COLONIALISM IN PSYCHOLOGY: BEWARE MACLEOD AND WILBRAHAM - Parker, Ian (PINS-Psychology in Society, 2025)
What could be worse than that work in what now pretends to be “critical psychology” is taken up uncritically and that radicals who have struggled for years to make sense of what the discipline does ideologically eventually learn to speak proper English? It would be gratifying perhaps to those of us churning out critical work from Manchester to imagine that the birthplace of capitalism could also provide the tools for those in the colonies to dismantle it. It would be gratifying in the short term, but it is a form of gratification cruelly denied by Macleod and Wilbraham’s response to my work. This is so far, so good, and all the better for a genuinely critical perspective in psychology. But wait a minute; if what I have written so far has been of some use to these South African criticals precisely by virtue of the simplifications and lacunae that characterise it, surely the most robust critical response to their critique might also be useful to them. It is in that spirit of admiration for what they have produced as they resist being taken in by my work so far that I want to tackle some problems with one of the main theoretical resources Macleod and Wilbraham mobilise against me.